2021
DOI: 10.3390/ma14164597
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Welding of 2205 Duplex Stainless Steel: Feasibility of Butt Joint Groove Filling in Comparison to Gas Tungsten Arc Welding

Abstract: This work investigates the feasibility of using friction stir welding (FSW) process as a groove filling welding technique to weld duplex stainless steel (DSS) that is extensively used by petroleum service companies and marine industries. For the FSW experiments, three different groove geometries without root gap were designed and machined in a DSS plates 6.5 mm thick. FSW were carried out to produce butt-joints at a constant tool rotation rate of 300 rpm, traverse welding speed of 25 mm/min, and tilt angle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…It can be noted that the present phases α and γ in the BM are 50.4% and 49.6%, respectively. These values are close to that reported by other authors for the as-received DSS 2205 [1,7]. In addition, from Table 5, the α: γ phase ratio for the welded butt joint at 600 rpm, 50 mm, and 14 kN is 49.4:50.6, while the joint welded at 300 rpm, 25 mm/min, and 20 kN has a ratio of 48.0:52.0.…”
Section: Ferrite Contentsupporting
confidence: 89%
See 4 more Smart Citations
“…It can be noted that the present phases α and γ in the BM are 50.4% and 49.6%, respectively. These values are close to that reported by other authors for the as-received DSS 2205 [1,7]. In addition, from Table 5, the α: γ phase ratio for the welded butt joint at 600 rpm, 50 mm, and 14 kN is 49.4:50.6, while the joint welded at 300 rpm, 25 mm/min, and 20 kN has a ratio of 48.0:52.0.…”
Section: Ferrite Contentsupporting
confidence: 89%
“…This groove-like defect can surely degrade the tensile properties of the weld joint. Some works [1,32] reported that groove-like defects are primarily generated with insufficient heat input during the stirring process. In this condition, the plastic material could not easily flow in the SZ to build the sound butt joint by the tool pin.…”
Section: Visual and Macrostructure Examinationmentioning
confidence: 99%
See 3 more Smart Citations